FIQIH DAN TASAWUF DALAM PENDEKATAN HISTORIS - Ali Masud; Ah Zakki Fuad (LPPM UNISDA, 2018)
Empirically, Fiqh and Tasawuf are different. Fiqh has the character as symbolic, legalistic, exoteric, and formalistic. It tends to see a certain action from point of view of condition and administrative, legal and illegal. In fact, such an understanding is not acceptable as a result of the limitation in understanding Fiqh. Fiqh is a basic understanding toward messages of Syaria’at or God’s Khittab which deals with the heresy’s activities from the detailed argumentations. On the other hand, there is an assumption that tasawuf is identical with the resignation of static life. Tasawuf has the character of being exoteric emphasizing on spiritualistic. The sufi community do other Islamic rituals and they try to interpret their meanings by themselves. For the sufi community, those rituals are done to resign themselves to Allah. That is why an activity of doing ablution is intended not only to clean up physical organs but also internal aspects. What the sufi community do is principally out of their ego area to close themselves to the God.